Comparative Outcomes in Children and Adults With Anti-N-Methyl-D-Aspartate (anti-NMDA) Receptor Encephalitis. (October 2017) - Gordon-Lipkin, Eliza; Yeshokumar, Anusha K.; Saylor, Deanna; Arenivas, Ana; Probasco, John C.
This study compared neurologic disability and adaptive function in children and adults >1 year following anti- N -methyl-d -aspartate receptor (anti-NMDAR) encephalitis diagnosis. Retrospective record review identified 12 patients with anti-NMDAR encephalitis. At last follow-up, all surviving patients had "good" modified Rankin Score (0-2). Four children, 6 adults, and their families participated in a telephone interview. Median duration since diagnosis was similar for children (2.42 years, interquartile range 2.12-3.32) and adults (3.55 years, interquartile range 2.08-5.50 years). 3/4 (75%) pediatric and 3/5 (60%) adult patients reported neuropsychiatric symptoms (fatigue, emotional lability, short-term memory deficits or concentration deficits). On the Adaptive Behavior Assessment System (ABAS-3), although overall adaptive function was intact for adults (general adaptive composite standard score: median 104.5, interquartile range 98.8-112.5), the median for children was below average (General Adaptive Composite Standard Score: median 82.0, interquartile range 79.0-89.0). Children with anti-NDMAR encephalitis may have long-term effects impacting daily life while adults regain normal function.